ANALISIS PENALARAN STATISTIS SISWA SMA DENGAN GAYA BELAJAR VISUAL, AUDITORIAL, DAN KINESTETIK DALAM MEMECAHKAN MASALAH KONTEKSTUAL - Tsaniyah, Rohmatus; Ekawati, Rooselyna; Sofro, A’yunin (LPPM Universitas Bina Bangsa, 2024)
More and more problems cannot be solved without collecting and processing data. Therefore, a data processing science called statistics is needed. There are several statistical abilities that an individual needs to have in order to help an individual in solving problems, one of which is statistical reasoning. A person's statistical reasoning can be seen from how a person solves problems. One of the things within a person that can influence the way a person solves problems is learning style. From these several things, it is suspected that there is a connection between learning style and a person's statistical reasoning. Therefore, researchers developed this research with the aim of finding out whether there is a relationship between learning styles and statistical reasoning. This research uses mixed methods, a combination of quantitative and qualitative methods. The quantitative method used was the One-Way Anova test and the result was that Fratio < Critical F. So all visual, auditory and kinesthetic learning styles have the same influence on statistical reasoning. Meanwhile, the qualitative method also supports previous results that the statistical reasoning profiles of students with visual, auditory and kinesthetic learning styles are almost the same